Al-GHAZALI DAN OPOSISINYA TERHADAP FILSAFAT - Jamhari Jamhari (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2015)
Al-Ghazali was a controversial figure. Many scientists adore him but many others condemn him. Hundreds of books have been discussed about his thinking. Thus it until now still remains interesting to study. Prominent Al-Ghozali has been and is still one of the biggest figures in the Muslim world similar to the position of August and Aquinas in the Christian world. Even some schoolars from Islam (particularly Sunni) and from Europe have looked Ghazali as a multidimensional characters, he was a theologian, philosopher, sufi and jurist. However, some Muslims consider al-Ghazali as the cause of the decline of Islam, because of his book Tahafut al-Falasifah. In fact Muslims are not ready with different opinions. Due to the differences of opinion in theology, hundreds or even thousands of peoples have been the victims throughout the Islamic history. The paper will discuss about the controversial thought of Al Ghazali, namely: the problem of natural immortality, The God’s knowledgement on universal problem not the particular one, and the resurrection of the body in hereafter. In spite of the strong opposition of al-Ghazali’s philosophy, the opposition only covers on the issues of his metaphisics thought and concealing another aspect such as using Aristotelian logic to think about God.